PEMBUATAN OBAT TRADISIONAL BERBAHAN PEGAGAN EMBUN BAGI MASYARAKAT DI KENAGARIAN VII KOTO TALAGO KECAMATAN GUGUK KABUPATEN 50 KOTA - Yufri Aldi; Salman Salman; Elsa Badriyah; Aditya Alqamal Alianta; Elidahanum Husni (LPPM Universitas Andalas, 2022)
The purpose of this activity is so that people can process plants in a measurable and precise manner, and the frequency of use is by the severity of the disease and the length of time for drug administration. Methods of activity in the form of training and counseling. The counseling material provided on the first day was about the immune system and the benefits and results of research from Centella asiatica, which had been published in reputable international journals. The training provided was on harvesting and making Centella asiatica powder based on Good Traditional Medicine Making Methods. In the second period, there were lectures on using traditional medicine and training in making powders, and how to fill capsules using capsule boards with Centella asiatica powder. After training and counseling in the second stage, the questionnaire was filled out with the same material as the questionnaire given in the first period. This activity was carried out in Kenagarian VII Koto Talago, Guguk District, 50 Kota. Participants were PKK cadres and Bundo Kandung in Kenagarian VII Koto Talago. In the first period, it was attended by 125 participants, and in the second period, as many as 55 people. Before counseling, participants were required to fill out a questionnaire containing knowledge about the immune system and how to use traditional medicine. From the training and counseling given to the participants, it can be concluded from the questionnaire results that they have understood the body's immune system protects the body from infection by microorganisms. They have also been able to make powder and put it in capsules so that they become ready-to-use Centella asiatica capsules.